Crossed Connections From Insular Cortex to the Contralateral Thalamus - Adeyelu, Tolulope; Gandhi, Tanya; Lee, Charles C. (Frontiers in Neural Circuits, 2021)
Sensory information in all modalities, except olfaction, is processed at the level of the thalamus before subsequent transmission to the cerebral cortex. This incoming sensory stream is refined and modulated in the thalamus by numerous descending corticothalamic projections originating in layer 6 that ultimately alter the sensitivity and selectivity for sensory features. In general, these sensory thalamo-cortico-thalamic loops are considered strictly unilateral, i.e. no contralateral crosstalk between cortex and thalamus. However, in contrast to this canonical view, we characterize here a prominent contralateral corticothalamic projection originating in the insular cortex, utilizing both retrograde tracing and cre-lox mediated viral anterograde tracing strategies with the Ntsr1-Cre transgenic mouse line. From our studies, we find that the insular contralateral corticothalamic projection originates from a separate population of layer 6 neurons than the ipsilateral corticothalamic projection. Furthermore, the contralateral projection targets a topographically distinct subregion of the thalamus than the ipsilateral projection. These findings suggest a unique bilateral mechanism for the top-down refinement of ascending sensory information.